Pragmatic Failures Experienced by Jacob in Jodi Picoult’s Novel House Rules - Riza Suryandari; Adi Sutrisno (Universitas Gadjah Mada, 2018)
Pragmatic failures are often discussed in the context of cross-cultural studies. However, pragmatic failures have also been evident in other circumstances. People who are diagnosed with Asperger Syndrome, for example, also often experience pragmatic failures, even when they converse with others who come from the same geographical area and share the same culture. This paper examines pragmatic failures produced by Jacob, a character diagnosed with Asperger syndrome (AS) in Jodi Picoult’s novel House Rules. The data were excerpts taken from the novel that show Jacob’s failures to understand the other speakers. The data were classified into 12 categories of pragmatic failures: sarcasm, idioms, common phrases, metaphors, hyperbole, words with multiple meanings, the maxim of quality, maxim of quantity, maxim of relation, maxim of manner, joke, and indirect speech acts. The results showed that the most frequent type of pragmatic failures that Jacob produces in the novel is the infringement of the maxim of relation. In other words, Jacob often produces irrelevant utterances.